(untitled) (Journal of EAHIL, 2024)
Dear all, for this issue’s “Publications and new products” column I’ve searched the web and selected news and articles regarding several current topics which I hope would be of your interest. I would also like to take this occasion to wish you and your family all the best for the New Year.